2013
DOI: 10.1590/s1806-00132013000300008
|View full text |Cite
|
Sign up to set email alerts
|

A dor dificulta a prática de atividade física regular na percepção de idosas longevas

Abstract: BACKGROUND AND OBJECTIVES: The number of people aged 80 years or above is increasing worldwide. Considering that most such longevous people are physically inactive, and that this is a major risk for the appearance of different diseases and body pains, the regular practice of physical activities may favor the health of such population. So, this study aimed at evaluating pain perception as a barrier for the practice of regular physical activities by physically inactive longevous women. METHODS: This is a descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
12

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 10 publications
(32 reference statements)
1
3
0
12
Order By: Relevance
“…8,20 In this study, the educational history of the group analyzed was marked by a low educational level, with the majority (79.2%) reporting a maximum level of schooling of having concluded the early grades of elementary school, or never having studied, a similar result to previous findings related to Brazilian elderly persons. 21 Studies have shown that lower levels of education are associated with less physical activity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…8,20 In this study, the educational history of the group analyzed was marked by a low educational level, with the majority (79.2%) reporting a maximum level of schooling of having concluded the early grades of elementary school, or never having studied, a similar result to previous findings related to Brazilian elderly persons. 21 Studies have shown that lower levels of education are associated with less physical activity.…”
Section: Discussionsupporting
confidence: 85%
“…Low socioeconomic status; functional impairment; presence of disease; fear of injury; lack of company; an unsuitable local environment or climate and a lack of infrastructure are some of the barriers to physical activity identified by the elderly. [6][7][8] In Brazil, 72% of causes of deaths are attributed to CNCDs. In such a climate, a strategic action plan for dealing with chronic noncommunicable diseases (CNCDs) in Brazil 2011-2022 was created.…”
Section: Introductionmentioning
confidence: 99%
“…Entre idosos há maior incidência de dores e desconfortos, pois esses indivíduos geralmente são mais suscetíveis a doenças características do processo de envelhecimento. Essas dores podem influenciar o nível de energia, aumentando a fadiga, e fazendo com que eles desenvolvam atividades de lazer que não lhes exijam muito desgaste físico 26,27 . Apesar disso, considera-se como aspecto importante deste estudo o fato de o domínio físico ter apresentado os coeficientes de correlação mais elevados com as atividades físicas vivenciadas no lazer, assim como com as atividades artísticas, manuais e intelectuais.…”
Section: Artísticasunclassified
“…The author concludes that it is possible to decrease pain intensity because moderate aerobic physical exercise maintained for more than 10 minutes may activate endogenous pain control mechanisms, may improve strength and muscle resistance, wellbeing and quality of life, improving ability to perform BDLA 17 . Similarly, studies show that the elderly practicing physical activities had lower prevalence of CP in addition to better quality of life 13,18 . A study in the city of Florianópolis 10 with 1656 elderly has observed that being physically active was associated to lower chronic pain prevalence 10 .…”
Section: Discussionmentioning
confidence: 98%